Reproductive biology of teleost fishes - Wootton, R. J. (Robert J.); Smith, Carl, 1966- (Hoboken, NJ : John Wiley & Sons Inc., 2015)
Reproductive Biology of Teleost Fishes is the first integrated review of the reproductive biology of the bony fishes, which are the most species-rich and diversified group of vertebrates. Teleosts display remarkable variation in their modes of reproduction, and this volume is intended to provide a framework for understanding the remarkable reproductive diversity of this group. It describes their reproductive biology using, wherever possible, phylogenetic analyses and life-history theory as a means to interpret the information. The book addresses the genetic, physiological, behavioural, ecological, evolutionary and applied aspects of teleost reproduction in a comparative framework that emphasises the adaptive basis of reproductive diversity. Reproductive Biology of Teleost Fishes provides a comprehensive synthesis of fish reproduction that will be of great interest to life scientists, particularly ecologists, evolutionary biologists, physiologists and advanced undergraduates, postgraduates and research workers requiring a comprehensive overview of fish reproduction. The book is suitable for courses in fish biology and ecology, reproductive physiology and reproductive genetics. It also addresses applied questions and will be of value for courses on fisheries science and aquaculture. Libraries in all universities and research establishments where biological sciences, fisheries science and aquaculture are studied and taught should have several copies of this important book on their shelves.
Direct intersexual selectionIndirect intersexual selection; Arbitrary mate choice; Male mate choice and female ornaments; Mutual mate choice and the'double process' of sexual selection; Mate choice copying; Intrasexual selection; The interaction of intra- and intersexual selection; The strength of sexual selection and the operational sex ratio; Courtship; Sexual signals and reproductive isolation; Fertilisation; Sperm competition; External fertilisation; Internal fertilisation; Quasi-internal fertilisation; Male mating polymorphisms; Female mating polymorphisms; Sexual conflict.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Osteichthyes -- reproduction; Fishes -- Reproduction; Osteichthyes -- Reproduction; Electronic books